ASSESSMENT OF THE ECOLOGICAL CONDITION OF THE RESIDENTIAL AREA OF DNIPRO CITY - Myronova, I.; Mіlyutinа, V. (My University, 2021)
Purpose. Assessment of the ecological condition of the residential area “Topolia” of Dnipro city with application of the method of bio-indication and development of recommendations for improving the condition of the outdoor air in the city. The methodology of research. Plant objects as indicators of ecological loading on the territory of the residential area “Topolia” of Dnipro city were examined with application of the method of bio-indication “Sterility of plant pollen”. The method of determining the level of atmospheric air toxicity is based on establishing the proportion of sterility of pollen of indicator plants that grow in the examined area. The examination of sterile and fertile pollen cells of higher plants with taking into account their resistance (sensitivity) to the action of adverse factors was performed by using a binocular microscope “Biolam” R-14 with illumination and application of a counter. Statistical data processing was performed by using the method of alternative variation. The percentage of sterile cells of pollen grains of phytoindicators was determined, a comprehensive assessment of the ecological situation of the residential area was conducted according to the indicators of toxic-mutagenic background with application of the assessment scale of bio-indicators and ecological situation. Findings. The number and percentage of sterile cells of pollen grains of higher indicator plants in the places of sampling on the residential areas “Topolia-1”, “Topolia-2”, “Topolia-3” in Dnipro were established. Conditional damage indicators of the bio parameter of each plant object and integrated conditional indicators of phytoorganism damage at each sampling site were calculated. The analysis of the integrated conditional indicators of damage revealed that one point (“Topolia-3” microdistrict, building 57, near the “ATB” store) has a “dangerous” state of the outdoor air, which is related to the number of vehicles. It is possible to improve the condition of the air due to the following recommendations: responsible attitude of each vehicle owner to the technical condition of the car, application of cleaner fuels or movement in the city by walking, by bicycle and public electric transport more often; landscaping of territories of the different functional purpose. The originality. Conditional index of damage of indicator plants with increasing the distance from the place of the greatest accumulation of motor transport of the residential area “Topolia” of Dnipro city decreases according to the linear dependence and reaches the normative indicator at a distance of 200 m. Consideration of this dependence will allow predicting the toxic-mutagenic background of the outdoor air. Practical implications. The results of the research allow us to assess the ecological condition of the residential area “Topolia” in Dnipro city and to develop recommendations for improving the condition of the air within the city.
Keywords: higher plants; oudoor air; bio-indication; toxicity; ecological condition; danger